2003
DOI: 10.1088/0953-2048/17/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Transport ac loss in a long cylinder with a hard superconducting core and normal conducting shell

Abstract: The power loss is analytically derived for a long cylinder with a hard superconducting core and a normal conducting shell under an applied ac current of amplitude I m . The core obeys the critical-state model with a constant critical-current density J c and the shell obeys the Maxwell equations and the Ohm law with a constant permeability µ 0 and conductivity σ . The dependence of the normalized ac loss per cycle per unit length upon I m /I c (I c being the critical current), the normalized frequency, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The decrease of q * with increasing f at i m * Ͼ 1.5 may be related to the loss occuring in the normal metal Ag in the shell. 15 The q * at i m * Ͻ 1 to be lower than that calculated from the PL E͑J͒ and the CS q calculated from Eq. ͑1͒ may come from a field dependent J c , which is not considered in the derivation of Eq.…”
Section: ͑13͒mentioning
confidence: 71%
“…The decrease of q * with increasing f at i m * Ͼ 1.5 may be related to the loss occuring in the normal metal Ag in the shell. 15 The q * at i m * Ͻ 1 to be lower than that calculated from the PL E͑J͒ and the CS q calculated from Eq. ͑1͒ may come from a field dependent J c , which is not considered in the derivation of Eq.…”
Section: ͑13͒mentioning
confidence: 71%
“…The transport ac loss in a long cylinder with a hard superconducting core and a normal conducting shell has been calculated analytically in [30] based on the CS model, the Ohm law, and Maxwell equations. It is concluded that the current in the shell is not an eddy current as commonly named but a transport current that is inductively coupled to the superconducting core.…”
Section: Further Comments On Transport and Eddy Currentsmentioning
confidence: 99%
“…However, it seems to us that the simplest case of a long cylinder with a hard superconducting core and a normal conducting shell has not been treated systematically. Therefore we have calculated analytically in [12] its transport ac loss as a function of current amplitude at various values of frequency and filling fraction of the superconducting core. Describing the essential feature of the normal current in the shell, we have concluded that it is not an eddy current, as commonly called, but a transport current that is inductively coupled to the supercurrent in the core.…”
Section: Introductionmentioning
confidence: 99%